Perfluoropropionic Acid (CF3CF2C(O)OH): Three Conformations and Dimer Formation - Carlos O. Della Védova; Rosana M. Romano; Hans-Georg Stammler; Norbert W. Mitzel (Molecules)
Perfluoropropionic acid (CF3CF2C(O)OH) has been investigated with a focus on its complex structural properties. As a formal derivative of propanoic acid, the incorporation of fluorine atoms imparts unique structural features, including three distinct monomeric conformations and a dimeric structure. This study presents experimental findings, supported by computational modeling, to explore these characteristics. The analysis includes an FTIR study of the isolated species in an Ar-cryogenic matrix and the low-temperature determination of its crystalline structure using single-crystal X-ray diffraction.